A multiple perspective modeling and simulation approach for renewable energy policy evaluation. (December 2016) - Alyamani, Talal; Damgacioglu, Haluk; Celik, Nurcin; Asfour, Shibab; Feiock, Richard
Highlights: We propose a novel and inclusive framework for renewable energy policy evaluation. Simulation modeling is used to assess renewable energy policy for the first time. The proposed method proposes quantitative analysis for various stakeholders. Florida is selected as a case study to show capabilities of the framework. Two solar programs and one energy efficiency program are assessed in detail. Abstract: Environmental issues and dependence on fossil fuel sources including coal, oil, and natural gas, are the two most prevalent energy issues that are currently faced by the United States. Incorporation of renewable energy sources, a non-economical option in electricity generation compared to conventional sources that burn fossil fuels, promises a viable solution for both of these issues single-handedly. Several energy policies have concordantly been suggested to reduce the financial burden of adopting renewable energy technologies and make such technologies competitive with conventional sources throughout the US. In this work, we present a novel simulation framework to help policymakers assess and evaluate policies from different perspectives of its stakeholders. The proposed framework is composed of four modules: (1) a database which collates the economic, operational, and environmental data; (2) elucidation of policy which devises the policy for the simulation model; (3) a preliminary analysis which makes predictions for consumption, supply, and prices; and (4) a simulation model. After the validity of the proposed framework is demonstrated, a series of planned Florida renewable energy policies are implemented into our framework as a case study. The results obtained from the simulation and conclusions drawn on the assessment of current energy policies are presented with respect to the conflicting objectives of different stakeholders.